‘Doing Business After the Fall: The Virtue of Moral Hypocrisy’ - Batson, C. Daniel (Journal of business ethics, 2006)
Moral hypocrisy is motivation to appear moral yet, if possible, avoid the cost of actually being moral. In business, moral hypocrisy allows one to engender trust, solve the commitment problem, and still relentlessly pursue personal gain. Indicating the power of this motive, research has provided clear and consistent evidence that, given the opportunity, many people act to appear fair (e.g., they flip a coin to distribute resources between themselves and another person) without actually being fair (they accept the flip only if it favors themselves). New evidence also indicates the power of moral hypocrisy in a situation more obviously relevant to business, resource allocation when one party has information about relative resource value that the other does not. Characteristics of modern business situations likely to encourage moral hypocrisy are outlined. We conclude that moral hypocrisy is not only a pragmatic virtue in modern business but is also fast becoming a prescriptive one.